Parameters of disavowal : colonial representation in South Korean Cinema (2018)
The career of South Korean filmmaker Im Kwont’aek spans over fifty years and one hundred films. His 1978 film The Genealogy (Chokpo) marks an important point in that career, for it shows a departure from the type of films he made throughout the 1960s and 1970s.1 Based on a novella by the Japanese writer Kajiyama Toshiyuki, the film reflects Im’s self-conscious and serious efforts to move away from the pro- duction of low-budget genre films.2 The Genealogy is one of his most thematically coherent and stylistically mature works of the 1970s, foreshadowing the preoc- cupation with national culture and tradition that would later be a prominent theme in his oeuvre. The film is set in the late colonial period, when the Japanese colonial government was increasing its pressure on Koreans to comply with the cultural assimilation policy aimed at converting Koreans into loyal imperial sub- jects. Its narrative focuses on Tani, a young Japanese government official who is assigned to convince the Korean patriarch Sŏl Chinyŏng to obey the new policy (ch’angssigaemyŏng in Korean) under which Koreans would adopt Japanese names. The film offers a complex narrative of Korean cultural resistance to colonial rule as shown from Tani’s conflicted perspective, which is both colonialist and sympa- thetic to the Korean opposition.3 In addition, the film’s exquisite mise-en-scène both features and manifests the themes of Korean tradition and cultural national- ism in visual terms.